Theoretical and Practical Aspects of Using Anatomically Detailed Puppets while Interrogating Extremely Vulnerable Persons - T. P. Matiushkova (Law and Safety)
The article is focused on one of the urgent tasks for domestic scholars and practitioners – the development and implementation of non-traumatic methods of interrogation. Thus, the author of the article defines theoretical and practical aspects of using anatomically detailed puppets during the interrogation of extremely vulnerable persons – minor victims and witnesses of rape, sexual abuse, corruption of minors, human trafficking, pornography, etc., including children with physical or (and) mental disorders.